ANALISIS TENTANG PERSEPSI MAHASISWA TERHADAP KARAKTER TANGGUNGJAWAB DALAM KEGIATAN ORGANISASI KEMAHASISWAAN DI FKIP UNIVERSITAS RIAU - Hadryan Hadryan; Ahmad Eddison; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstact : This research was motivated by student perceptions of the character of responsibility in student organization activities at the fakulty of teacher training and education at the university of riau. Where in student institutions each university has compiled a complete character education and it is hoped that students can form intellectuals who have superior personalities. The portion of character education in higher education is in fact decreasing. There are still many problems, namely the lack of responsibility in a mandate that is carried out so that it is said that the student is in an inactive status. The formulation of the problem in this study is how are students’ perceptions of the character of responsibility in student organization activities at FKIP, Riau Universisty. The purpose of the research in this study is to determine how students perceive the character of responsibility in student organization activities at FKIP, Riau Unicersity. The benefit of this research is to add insight and description of student’ perceptions of the character of responsibility in student organization activities at FKIP, Riau University. This research method is descriptive quantitative, the data collection instrument used in this research is a questionnaire consisting of 8 sub indicators with 18 statement. The population in this study were active students FKIP, amounting to 4.811 people. The sampel in this study was taken using the Non Probality Sampling teachnique, more precisely the quota sampling technique of 160 people. Based on the results of the study, it can be conluded that overall the data regarding the “160 student’ perceptions of the character of responsibility in student organization activities at FKIP, Riau University” is in the “very good” category. Respondent answered strongly agree (SS) plus Agree (s) namely 42,5% + 35% = 77,5%, this is in the range of 75.01% - 100%. Thus, it can be concluded that the interest of 160 samples of FKIP University of Riau at the “Very Good” level.Key Words: Analysis, Perception, student, character, responsibility, student organizations